Investigation on impact of endocrine disrupting compounds (EDCs) in aquatic environment - Lee, Kah Khim, 1991-, author; Salmiati, supervisor; Fakulti Kejuruteraan Awam (2015)
Project Paper (Sarjana Muda (Kejuruteraan Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2015